Alzheimer’s disease and oral manifestations: a bi-directional Mendelian randomization study - Huang, Jingxuan; Deng, Aiping; Bai, Yunshuang; Li, Chunyu; Shang, Huifang (Frontiers in Neurology, 2024)
Background Epidemiological studies have provided evidence suggesting an association between Alzheimer’s disease (AD) and various oral manifestations. However, conflicting conclusions have been drawn, and whether a causal association truly exists remains unclear. Methods In order to investigate the potential causal association between AD and prevalent oral diseases, we conducted a bi-directional two-sample Mendelian randomization analysis based on summary statistics from genome-wide association studies of AD (N = 63,926), as well as mouth ulcer (N = 461,103), oral cavity cancer (N = 4,151), and periodontal disease (N = 527,652). Results We identified that one standard increase in the risk of AD was causally associated with a reduced risk of oral cavity cancer (OR = 0.76, 95% CI: 0.63–0.92, p = 3.73 × 10−3). In the opposite direction, oral conditions were not causally associated with risk of AD. Conclusion The present findings contributed to a better understanding of the correlation between AD and oral conditions, specifically oral cavity cancer. These results also identified new avenues for exploring the underlying mechanisms of oral cavity cancer.